Anti-Angiogenic Activity of Rotenoids from the Stems of Derris trifoliata - Mittraphab, Yanisa; Ngamrojanavanich, Nattaya; Shimizu, Kuniyoshi; Matsubara, Kiminori; Pudhom, Khanitha (Planta Medica, 2018)
The plants in the genus Derris have proven to be a rich source of rotenoids, of which cytotoxic effect against cancer cells seem to be pronounced. However, their effect on angiogenesis playing a crucial role in both cancer growth and metastasis has been seldom investigated. This study aimed at investigating the effect of the eight rotenoids (1–8) isolated from Derris trifoliata stems on three cancer cells and angiogenesis. Among them, 12a-hydroxyrotenone (2) exhibited potent inhibition on both cell growth and migration of HCT116 colon cancer cells. Further, anti-angiogenic assay in an ex vivo model was carried out to determine the effect of the isolated rotenoids on angiogenesis. Results revealed that 12a-hydroxyrotenone (2) displayed the most potent suppression of microvessel sprouting. The in vitro assay on human umbilical vein endothelial cells was performed to determine whether compound 2 elicits anti-angiogenic effect and its effect was found to occur via suppression of endothelial cells proliferation and tube formation, but not endothelial cells migration. This study provides the first evidence that compound 2 could potently inhibit HCT116 cancer migration and anti-angiogenic activity, demonstrating that 2 might be a potential agent or a lead compound for cancer therapy.
Keywords: rotenoid; Derris trifoliata; Leguminosae; cytotoxicity; anti-angiogenesis; cancer; cell migration